Trends and Effectiveness of School-Based Interventions for STI Prevention among Indonesian Adolescents: A Bibliometric and Systematic Review - Ilmi, Hamdin Pizzati (Varians Jurnal Kesehatan Masyarakat, 2026)
Sexually transmitted infections (STIs) among Indonesian adolescents remain a major public health concern due to low reproductive health literacy and inconsistent school-based education. This study synthesized trends and the effectiveness of school-based STI prevention programs using bibliometric and systematic review approaches. Data from four databases (2010–2025) were screened via PRISMA. 15 eligible studies, mostly quasi-experimental, involved adolescents aged 10–19 and used videos, games, print, or culturally adapted media. Interventions improved knowledge, moderately influenced attitudes, and rarely measured behavior. Interactive, multimedia programs with control groups had stronger impacts. Findings support integrating culturally relevant, interactive, and longitudinally evaluated STI education into national policy.